Effects of local and core body temperature on grip force modulation during movement-induced load force fluctuations - Cheung, S. S.; Reynolds, L. F.; Macdonald, M. A. B.; Twedie, C. L.; Urquhart, R. L.; Westwood, D. A. (European Journal of Applied Physiology, 2008)
Impaired manual functioning often occurs when the hands are exposed to cold temperatures, but the underlying mechanism is not clearly understood. Tactile feedback is thought to provide important information during object manipulations in order to scale and regulate grip forces; however, topical anaesthetic-induced tactile sensation impairments may not realistically simulate the systemic neuromuscular impairment of the whole hand that could occur during cold temperature exposure. In two experiments, we studied the impact of (1) local hand cooling [thermoneutral finger skin temperature, cold (<8°C)] and (2) core body temperature (thermoneutral core body temperature, pre-heated by 0.5°C, pre-cooled by 0.5°C) with cold hands on manual dexterity and the ability to control and co-ordinate grip forces during a cyclical load-lifting task. In Experiment 1 (n = 10), hand cooling significantly decreased Purdue Pegboard performance (P = 0.002), while increasing grip force by ~5 N during the cyclical load-lifting task compared to thermoneutral (P = 0.037). The temporal co-ordination of grip and load forces was unaffected by hand cooling. In Experiment 2 (n = 11), pegboard performance was impaired following hand cooling (P < 0.001), and to a greater extent when the body was pre-cooled (p < 0.001). However, neither grip force (P = 0.99) nor the temporal co-ordination of grasping and lifting forces (P = 0.85) were affected by core body temperature. These data support the existence of a robust centrally controlled feedforward system able to anticipate the dynamics of manual manipulations and accordingly regulate the temporal co-ordination of fingertip forces during object manipulation. This centrally controlled mechanism appears to differ from the mechanisms governing other aspects of manual dexterity.